Tourism growth and entrepreneurship: Empirical analysis of development of rural highlands - Jaafar, Mastura; Rasoolimanesh, Mostafa S.; Tuan Lonik, Ku Azam (ELSEVIER, 2015)
We investigated small tourism-related businesses in Kinabalu National Park, Sabah, to identify their characteristics and constraints. Awarded World Heritage Site status in 2000, Kinabalu National Park provides a wealth of economic opportunities to adjacent rural communities. Quantitative data from a sample of 145 tourism-related small business entrepreneurs from these communities revealed that most of these entrepreneurs were female, middle-aged or older, and poorly educated. Most used their own savings to establish and maintain their businesses, sustaining operations and staffing levels throughout the year despite seasonal slumps in tourist numbers, marginal profits, and a lack of tourism-specific knowledge and skills. Respondents received virtually no financial support or training from government sources and there were few incentives for the local community to participate in tourism-related activities. Government and related organizations should aim to reduce such constraints on the operations of small businesses to ensuremore sustainable tourismdevelopment in KinabaluNational Park.